Characterization and Analysis of Argania spinosa Shells from Souss-Massa Area: Application in the Adsorption of Methylene Blue in Aqueous Solution. (25th March 2022) - Ifguis, Ousama; Bouhdadi, Rachid; Ziat, Younes; George, Béatrice; Mbarki, Mohamed
Abstract : This study focused on the adsorption in aqueous solution of methylene blue (MB), a cationic dye used in the textile industry, by crushed Argan shells (used as raw materials) from the southern region of Morocco. These crushed Argan shells were first characterized by different technical analyses: elemental analysis, biochemical analysis, IR spectroscopy, thermogravimetric analysis, scanning electron microscopy, mercury porosimetry, and zetametry. The adsorption kinetics was then studied by varying the experimental parameters such as the dye concentration in solution. We note that at pH = 8, there is an elimination up to 232.6 mg/g, during an equilibrium time of 180 min. The correlation coefficient showed that the pseudosecond-order kinetic equation best describes the adsorption kinetics for the tested material. The adsorption isotherms of MB by Argan shells are suitably described by the Langmuir model which provide the best theoretical correlation of the experimental data. The thermodynamics of MB adsorption on Argan shells indicates a spontaneous and endothermic process. It was concluded that an increase in temperature leads to a greater adsorption of MB by the studied biosorbent.